Analysis of Poverty and Unemployment on Human Development Index in West Kalimantan in 2020-2022 - Alsa Muarti; Anisa Shafarianti; Evy Sulistianingsih (Jurnal Forum Analisis Statistik, 2023)
The Human Development Index (HDI) is built through a three-dimensional approach, namely knowledge, decent living standards, and longevity and healthy living. In the longevity and healthy life dimension, life expectancy at birth is the benchmark, and the expected years of schooling and average years of schooling are indicators used in the knowledge dimension. Meanwhile, a decent standard of living as measured by annual capita expenditure is an indicator in the HDI. West Kalimantan's HDI in 2020 to 2021 experienced a fairly low increase, then in 2021 to 2022, West Kalimantan's HDI experienced a very significant increase and even occupied the first position of the highest HDI increase in Kalimantan Island. The increase in West Kalimantan's HDI every year is influenced by a number of variables that affect HDI. The objective of this research is to examine the influence of poverty and unemployment on the Human Development Index (HDI) by analyzing the outcomes derived from the most effective panel data regression model. This study involves several phases, including data input, conducting multicollinearity tests, analyzing using panel data regression models, finding the best model with the Chow test, Hausman test, and Lagrange Multiplier test, as well as classical assumption tests, and output interpretation. The factors considered in this research comprise HDI (Y), poverty (X1), and unemployment (X2) in West Kalimantan. The examination indicates that the Fixed Effect Model (FEM) stands out as the most effective model, demonstrating an adjusted R-squared value of 99.14% where the variables of poverty (X1) and unemployment (X2) have a significant influence on HDI (Y).